Substrate-Based Ablation Reduces Recurrent Arrhythmia Compared to Focused Ablation in Ischemic Cardiomyopathy with Stable VT - Nichols, Emma Hitt (MD Conference Express, 2014)
Substrate-based ablation of ventricular tachycardia (VT) in patients with ischemic cardiomyopathy resulted in fewer VT recurrences and less rehospitalization compared with the conventional clinical VT ablation. This article present data from the Ablation of Clinical Ventricular Tachycardia Versus Addition of Substrate Ablation on the Long-term Success Rate of VT Ablation trial [VISTA; NCT01045668].